News shock spillovers: How the euro area responds to expected fed policy - Paul Rudel; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2024)
Monetary policy increasingly relies on steering market expectations about future policy. This paper identifies a monetary policy news shock based on a VAR model. A monetary news shock is equivalent to new information about the Fed's future monetary policy becoming available today. One example of a monetary news shock is a forward guidance announcement, where the Fed unveils its prospectively (binding) monetary policy, today. In this paper, we study the spillover effects of news shocks. We estimate the response of the euro area to an expected future policy tightening of the Fed. The U.S. news shock improves sentiment and business cycle expectations in the euro area, which is consistent with the notion of the Fed revealing favorable news by a tightening announcement. We also distinguish the news shock from a conventional U.S. policy surprise and find that they lead to diverging responses in the euro area.
Keywords: E43; E58; F42; 330; News shocks; spillovers; forward guidance; monetary policy; interest rates; expectations; central bank information effects